Methods to Analyse Time-to-Event Data: The Kaplan-Meier Survival Curve. (21st September 2021) - D'Arrigo, Graziella; Leonardis, Daniela; Abd ElHafeez, Samar; Fusaro, Maria; Tripepi, Giovanni; Roumeliotis, Stefanos
Abstract : Studies performed in the field of oxidative medicine and cellular longevity frequently focus on the association between biomarkers of cellular and molecular mechanisms of oxidative stress as well as of aging, immune function, and vascular biology with specific time to event data, such as mortality and organ failure. Indeed, time-to-event analysis is one of the most important methodologies used in clinical and epidemiological research to address etiological and prognostic hypotheses. Survival data require adequate methods of analyses. Among these, the Kaplan-Meier analysis is the most used one in both observational and interventional studies. In this paper, we describe the mathematical background of this technique and the concept of censoring (right censoring, interval censoring, and left censoring) and report some examples demonstrating how to construct a Kaplan-Meier survival curve and how to apply this method to provide an answer to specific research questions.